Perbandingan Efektivitas antara Omeprazol dan Lansoprazol terhadap Perbaikan Kualitas Hidup Penderita Rinosinusitis Kronik Akibat Refluks Laringofaring - Tantri Kurniawati; Teti Madiadipoera; Tonny Basriyadi Sarbini; Ongka M. Saifuddin (Majalah Kedokteran Bandung, 2012)
Laryngopharyngeal reflux (LPR) is the reflux of gastric acid through the esophagus that reaches laringopharyngeal area. The prevalence of LPR in the range 15–20%, and caused chronic rhinosinusitis (CRS). The incidence of LPR in patients with CRS has ranged between 37–72%. The prevalence of CRS 16,3% in adults and affecting quality of life. Omeprazole and lansoprazole are proton pump inhibitors (PPIs) for LPR’s therapy and also a therapy for CRS with LPR as the etiology. This research method was randomized clinical trial with open trial observation, conducted in June to December 2009. Twenty subjects with consecutive sampling method, divided into two groups (with simple randomization), the first group received omeprazole and the other lansoprazole. The subjects conducted complete physical otolaryngology examination, sino-nasal outcome test 20, reflux symptom index and reflux finding score with fiber optic rhinolaryngoscopy. These data was obtained before therapy, after 2 weeks and two months therapy, analyzed with Wilcoxon’s and Mann-Whitney’s test. There was no effectivity difference between omperazole and lansoprazole in reducing the level of severity of LPR (p>0.05), but quality of life improvement was better in lansoprazole than omeprazole group (p<0.05). In conclusion, lansoprazole is more effective than omeprazole in improvement of quality of life in patients with chronic rhinosinusitis caused by LPR